Financial Literacy and Digital Access as Key Factors in the Success of Women-Owned MSMEs - Silvana Syah; Goklas Siahaan (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
The purpose of this study is to analyze the influence of financial literacy and digital access on the success of women-led Micro, Small, and Medium Enterprises (MSMEs) in Depok City, Indonesia. The research method used is a quantitative approach with an explanatory research design, involving respondents who met the inclusion criteria. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. Financial literacy was measured through indicators related to basic financial knowledge, budgeting practices, record-keeping, loan management, and the use of digital financial products. Digital access was assessed through ownership of digital devices, the use of online platforms for marketing, the adoption of digital financial applications, participation in technology-related training, and the availability of stable internet connectivity. The results of the study show that both financial literacy and digital access have strong and significant positive effects on the success of women-led MSMEs, as reflected in a substantial proportion of variance explained. These findings support Human Capital Theory, the Resource-Based View, the Diffusion of Innovation Theory, and the Dynamic Capabilities Theory, emphasizing the importance of knowledge, skills, and technological adaptability in achieving sustainable competitive advantage. The results highlight the need for integrated empowerment programs that combine financial and digital literacy, strengthened digital infrastructure, and inclusive access to capital to enhance the competitiveness and resilience of women-led MSMEs in Indonesia.